Breast augmentation with silicone implants performed without drainage – retrospective analysis of 726 cases - Stepić, Nenad; Končar, Jovana D; Rajović, Milica; Novaković, Marijan (Vojnosanitetski pregled, 2017)
Background/Aim. Breast augmentation has been one of the most popular aesthetic procedures. Early complications, like infection, seroma, hematoma and capsular contracture like ones of the most frequent long term complications, might be related to wound drainage. The aim of the study was to investigate the rate of the complications of breast augmentation procedure performed without drainage. Methods. Retrospective analysis of all patients who had underwent breast augmentation in the period of 2003–2013 was performed. From the medical history of the patients, data related to their demographic characteristics, surgical technique and the rate of complications were collected. Wound drainage had not been used in any of the patients. The patients were followed at the discharge, after 7 days, three months and yearly thereafter. Wound seroma, wound hemathoma, wound infection and capsular contracture were followed. Results. There were 726 patients with the average age of 28.5 (22–48) years. Breast augmentation using silicone implants was performed with inframammary approach using subglandular and submuscular technique. The average implant size was 339 (200–520) cc. Subglandular augmentation had 545 (75%) of the patients while 181 (25%) received an implant in submuscular plane: completely submuscularly in 95/726 (13%) and by dual plane technique in 86/726 (12%) of the patients. In early postoperative period, there were no infection, five (0.7%) seromas and eight (1.1%) hematoma (five of them required surgical evacuation). There was no statistically significant difference between the two surgical techniques in terms of complication rate. During follow-up, there were three (0.4%) capsular contractures. Conclusion. The incidence of complications in our group of patients after breast augmentation is low even though no drainage was used. Still, further randomized trials are needed to prove the role of drainage in prevention of complications after breast augmentation.